2022
DOI: 10.3390/nu14142956
|View full text |Cite
|
Sign up to set email alerts
|

The Mediterranean Diet: An Update of the Clinical Trials

Abstract: The Mediterranean Diet (MedDiet) is a term used to identify a dietary pattern originating from the unique multi-millennial interplay between natural food resources and the eating practices of people living in the Mediterranean basin. Scientific evidence has described the healthy properties of the MedDiet and its beneficial role in several pathological conditions. Nevertheless, current socio-economic trends have moved people away from this healthy lifestyle. Thus, clinical and biological evidence supporting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 110 publications
(163 reference statements)
1
49
0
Order By: Relevance
“…In previous studies, the Mediterranean diet has been associated with reduced inflammation [ 69 ] due to the effect of some of its components. In our study, the analysis of plasma inflammatory markers, cytokines and chemokines, showed different profiles depending on the type of essential oil used in the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the Mediterranean diet has been associated with reduced inflammation [ 69 ] due to the effect of some of its components. In our study, the analysis of plasma inflammatory markers, cytokines and chemokines, showed different profiles depending on the type of essential oil used in the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that dietary induced weight loss is of stronger impact when addressing cardiovascular risk factors such as waist circumference, blood lipids, or blood glucose concentration, which was reported before [ 17 , 38 ]. In this regard, the Mediterranean Diet, in particular, showed beneficial effects on disease-related interventions with a focus on nutrition, with cardiovascular disease and MetS being the most investigated diseases for Mediterranean Diet [ 39 ]. The beneficial effects could be primarily related to its anti-inflammatory and anti-oxidant properties, as well as the effectiveness of this dietary pattern in controlling waist circumference and obesity [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the Mediterranean Diet, in particular, showed beneficial effects on disease-related interventions with a focus on nutrition, with cardiovascular disease and MetS being the most investigated diseases for Mediterranean Diet [ 39 ]. The beneficial effects could be primarily related to its anti-inflammatory and anti-oxidant properties, as well as the effectiveness of this dietary pattern in controlling waist circumference and obesity [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The management of myocardial infarction includes immediate revascularisation and the long-term secondary prevention of atherosclerotic vascular disease in the form of prophylactic medication and lifestyle intervention—i.e., smoking cessation, regular exercise, and a Mediterranean-type diet [ 2 ]. The Mediterranean diet is entangled with the way of life in Mediterranean countries [ 3 , 4 , 5 ] and is associated with favourable glucose and lipid metabolism (i.e., lower fasting plasma glucose levels, lower low-density lipoprotein (LDL) cholesterol and triglycerides levels, and low high-density (HDL) cholesterol levels) [ 6 ], improved vascular function [ 6 ], and reduced cardiovascular disease morbidity and mortality [ 7 , 8 , 9 , 10 ]. Pertinent guidelines for cardiovascular disease prevention, therefore, recommend Mediterranean diet for all patients after myocardial infarction [ 2 ], as it was shown to be effective for both the primary and secondary prevention of cardiovascular diseases [ 7 , 11 , 12 , 13 ], even as a modifier of genetic risk for cardiovascular disease [ 14 ].…”
Section: Introductionmentioning
confidence: 99%